Treatment of family hypercholesterolemia with PCSK9 inhibitors: an integrative review (Research, Society and Development, 2021)
Familial Hypercholesterolemia is responsible for the increase in the levels of total cholesterol and LDL-cholesterol, which can cause a sharp increase in cardiovascular diseases. PCSK9 (convertase 1) is a highly expressed gene in liver, intestine and kidney. When synthesized and mutated, these small genetic variations end up helping in the regulation of LDL-Cholesterol, in addition, PCSK9 binding to LDL-Receptor can occur, thus decreasing the density of these receptors on the surface of hepatocytes. Justification: FH is considered a worldwide health problem where in Brazil we have an estimated 250,000 to 300,000 people with the disease that can lead to serious cardiovascular problems. Objective: The aim of the present work is to identify and report considerations about the latest in the treatment of familial hypercholesterolemia with PCSK9 inhibitors through an integrative literature review. Methodology: the guiding question of the research was “What can we find most current in the treatment of familial hypercholesterolemia with PCSK9 inhibitors?”, we used the following words as descriptors for the search in the PUBMED, SciELO and LILACS databases: “Hypercholesterolemia Family", "Cardiovascular Diseases" and "PCSK9 Inhibitors". In total, according to the inclusion and exclusion criteria, we obtained 8 articles for analysis.